A review on the recent applications of gluten-free flour, functional ingredients and novel technologies approach in the development of gluten-free bakery products - Ronie, M.E.; Zainol, M.K; Hasmadi Mamat (Rynnye Lyan Resources, 2021)
Gluten is detrimental to people who suffer from gluten-related disorders. Recently, the upsurge in demand for gluten-free products can be traced not only from the population that suffered from gluten-related disorders but also people who prioritize healthy lifestyles and practising gluten-free diets. One of the most challenging tasks in the development of gluten-free products is their quality. The purpose of this review is to describe the application of gluten-free flours in common bakery products such as bread, cakes, and biscuits. This article does summarize some functional ingredients such as hydrocolloids, protein, and enzymes and also the applications of novel technological approaches including high-pressure treatment, sourdough fermentation and extrusion technology. Overall, different approaches utilized in the improvement of gluten-free bakery products will lead to various quality outcomes.